From the Vilna Ghetto to Nuremberg: Memoir and Testimony. Abraham Sutzkever - Kassow, Samuel D. (Holocaust and genocide studies, 2023)
Abraham (Avrom) Sutzkever (1913-2010) was among the most remarkable poets of the twentieth century. Though he left Vilna in 1946, he remained inextricably